Arteriovenous Fistula Self-Care Behaviors in Patients Receiving Hemodialysis Treatment: Association With Health Literacy and Self-Care Agency - Bülbül, Elif; Ayvaz, Meryem Yıldız; Yeni, Tuğba; TÜREN, SEVDA; Efil, Sevda (Sage Publications Ltd., 2022)
Background: Arteriovenous fistula-related self-care behaviors, self-care agency and health literacy are important for vascular access patency, which is vital in the continuation of hemodialysis treatment. The purpose of this study was to determine the arteriovenous fistula-related self-care behaviors of patients receiving chronic hemodialysis treatment and the relationship between these behaviors and their health literacy and self-care agency levels. Methods: In this descriptive correlational study, the data were collected from 216 chronic hemodialysis patients. Results: The rate of the patients who had good self-care behaviors levels was 83.96%. The sociodemographic variables that were significantly related to AVF-related self-care behaviors were education, employment status and age. It was found that the patients who had had AVF for a longer time had better self-care behaviors regarding their management of symptoms and findings (p < 0.05). As the self-care agency of the patients (r = 0.612, p < 0.001) and their health literacy (r = 0.421, p < 0.001) increased, their AVF-related self-care behaviors also increased. Conclusion: Age, education status, health literacy and self-care agency were identified to affect AVF-related self-care behaviors.
Keywords: Arteriovenous Fistula; Health Literacy; Self-Care